2020
DOI: 10.1093/trstmh/trz134
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection in asymptomatic persons in Myanmar, 2018

Abstract: Background Zika virus (ZIKV) is a mosquito-borne flavivirus. Outbreaks of ZIKV infection have occurred in Africa, Southeast Asia, the Pacific Islands, the Americas and the Caribbean. Although most ZIKV infections are asymptomatic, cases of neurological manifestations have been described. The aim of the present study was to identify the prevalence of ZIKV infection among the asymptomatic persons in Myanmar in 2018. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…25 Contrary to the Malaysian results, a number of studies in Southeast Asia in Myanmar (15.8%), Laos (4.5%), Indonesia (9.9%), Cambodia (63%), and Thailand (70.4%) have reported relatively high rates of ZIKV seroprevalence among asymptomatic adults and children. 19,[26][27][28][29] In the present study of confirmed ZIKV cases, the IgM ratio was higher against ZIKV than DENV and JEV, with some samples indicating the presence of IgMs against ZIKV, DENV, and JEV, all of which belong to the same Flaviviridae family. This could be due to coinfection or sequential infection of the patients by DENV and ZIKV since they are transmitted by the same mosquito species circulating in the same area.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…25 Contrary to the Malaysian results, a number of studies in Southeast Asia in Myanmar (15.8%), Laos (4.5%), Indonesia (9.9%), Cambodia (63%), and Thailand (70.4%) have reported relatively high rates of ZIKV seroprevalence among asymptomatic adults and children. 19,[26][27][28][29] In the present study of confirmed ZIKV cases, the IgM ratio was higher against ZIKV than DENV and JEV, with some samples indicating the presence of IgMs against ZIKV, DENV, and JEV, all of which belong to the same Flaviviridae family. This could be due to coinfection or sequential infection of the patients by DENV and ZIKV since they are transmitted by the same mosquito species circulating in the same area.…”
Section: Discussionmentioning
confidence: 89%
“…31 Consequently, an in-house ZIKV/DENV/JEV IgM-capture ELISA was used, followed by 90% neutralization tests against ZIKV, four serotypes of DENV, and JEV. 18,19 The neutralization test undoubtedly plays an important role in confirming ZIKV infections in this situation by determining ZIKV IgM crossreactive with other flaviviruses to rule out ZIKV infection. Zika virus IgM persists for up to approximately 12 weeks, 32 and positive ZIKV IgM was detected in apparently healthy people.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations